A Review on Digital Mentoring in Educational Field - Breez Mohan Hazarika (AG Volumes, 2022)
One of the most significant benefits of digital mentoring is the opportunity to interact with experienced mentors whenever and wherever they may be located in the globe. Mentors and mentees in the same region may connect, network, and discuss organisational potential with one other, which is a benefit. Mentees have a greater chance of finding a mentor with a unique skill set and experience because of the interconnectedness of our environment. As a result, participants will have greater choice over the sort of adviser they work with and the lessons they take away from their experience. When the COVID-19 epidemic struck, it pushed forward the digital transformation age and the transition from mentorship to e-mentorship. The mentees who are pursuing graduate degrees are among the ones most impacted by this predicament. When e-mentoring is used in this way, it allows both the mentee and the mentor to collaborate on their academic work while avoiding the constraints of distance and time zones. So much has changed in the digital era. "Learning and development" environments are becoming more common in the workplace, and mentors are adapting their methods to reflect this trend. This paradigm shift has just been given a boost by the digital era. It is generally accepted that a mentor acts as an advisor to students in order to assist them achieve their career goals. The purpose of the mentoring connection that exists between a teacher and a student goes much beyond the simple act of instructing the student and extends to the student's improvement in both their educational and personal development.